Participatory evaluation and selection of improved haricot bean varieties at liben district, lowland agro ecology of Guji zone, Oromia regional state, Ethiopia - Kebede, Basha; Korji , Dembi; Amare, Girma (Asian Journal of Agriculture and Rural Development, 2018)
The activity was conducted in Liben district to evaluate the yield performance of improved haricot bean varieties. 25 pastorals and agro pastorals were selected from Measa kebele with collaboration of Liben Pastoral and Agro Pastoral Office, Zonal Mobile Supporting Team and kebele leaders. The 25 pastoral and agro pastorals were grouped into one PAPRG. Then 25 PAPRG members were regrouped into three experimental pastorals and agro pastoralists. Training were given for PAPRG members. Exchange visit was arranged to share experience on the work each PAPRG. Haramaya, Awasa Dume, Ebado varieties were evaluated with standard check variety. Descriptive statistics and direct matrix ranking was used to analysis the data. Local variety give the highest yield (31kg/ha). PAPRG criteria for haricot bean production was market demand, color, disease/insect reaction, drought resistance. Accordingly, Ebado variety was preferred by PAPRGs based on marketability while Local check and Awasa Dube were selected as first and second respectively based on drought resistance, number of pod/plant, higher yield and resistance to insects. Haramaya variety was susceptible to insects. Pastoralists and agro pastoralists should use Ebado variety to increase their income and local variety for household consumption.